Nghiên cứu thành phần hóa học cây chóc máu (Salacia chinensis L.) thu tại Thừa Thiên Huế - Minh và cống sự, Trần Thị (Vietnam Journal of Chemistry, 2014)
Three triterpenoids, betuline, 29-nor-21-aH-hopane-3,22-dione and 21-aH-hop-22(29)-ene-3b,30-diol have been isolated from the n-hexane extract of Salacia chinensis stems. The structures of these compounds have been elucidated on the basis of spectral studies.